Pengaruh Kinerja Keuangan Terhadap Harga Saham Pada Perusahaan Sektor Properti Dan Real Estate - Suhar; Ahmad Syahrizal; Novi Ayu Lestari (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to examine the effect of the financial performance of the liquidity ratio, Debt to assets ratio, Return on investment on stock prices in property and real estate sector companies listed on the Indonesia Stock Exchange for the 2016-2021 period. The independent variable used is financial performance and the dependent variable used is stock price. The data used in this research is secondary data. The population and sample are 8 samples multiplied by 6 years, so there are 48 samples. The sample was selected using purposive sampling method. The analytical method used in this study is multiple linear which is processed using SPSS IBM 22 and Microsoft Excel 2010. The results of this study indicate that the independent variables of financial performance from liquidity ratios, Debt to assets ratio, Return on investment have a significant effect on stock prices .